Paraphlomis anisochila (Lamiaceae), a new species from Hunan, China - Ang Liu; Hai-Bo Chen; Fan Zhang; Ya-Ping Chen (PhytoKeys)
Paraphlomis anisochila, a new species from the subtropical evergreen broad-leaved forests of Hunan Province, southern China, is described and illustrated. Morphological comparisons indicate that P. anisochila is most similar to P. seticalyx, whereas molecular phylogenetic analyses based on a comprehensive sampling and two nuclear ribosomal DNA regions (ITS and ETS) place it as the sister species of P. yingdeensis. Paraphlomis anisochila is characterized by its unequal corolla lips, distinguishing it from all other Paraphlomis species. Additionally, it differs from P. seticalyx in lamina shape, petiole and calyx length, and from P. yingdeensis in plant indumentum, calyx tooth apex, and corolla color.